Hexagonal Boron Nitride Doped PVA Composite Nanofibers for Antimicrobial and Biocompatible Applications - Evcimen Duygulu, Niluefer; Balkas, Merve; Ciftci, Fatih; Kucak, Mine (WILEY-V C H VERLAG GMBH, 2025)
In this study, boron nitride nanoparticles (BNNPs) doped polyvinyl alcohol (PVA) composite nanofibers were fabricated cost-effectively and straightforwardly using the electrospinning technique. The uniform PVA/BN composite nanofibers were measured as 376.26 +/- 59.20 nm, observed through Scanning Electron Microscopy (SEM). The presence of hexagonal boron nitride (h-BNNPs) was confirmed using transmission electron microscopy (TEM) and X-ray diffraction (XRD). Fourier transform infrared spectroscopy (FT-IR) results indicated enhanced structural stability and the formation of new functional groups. Water absorption tests showed that the hydrophobic nature of BNNP is dominant. The degradation rate of the PVA/BN was found to be faster than PVA nanofibers. Antibacterial tests demonstrated that PVA/BN fibers exhibited inhibition zones against Escherichia coli (8.78 mm), Staphylococcus aureus (6.82 mm), and Candida albicans (21.54 mm). The Minimum Inhibitory Concentration (MIC) results reinforced these findings, with PVA/BN fibers achieving an impressive inhibition rate of 89.56% against E. coli. Utilizing the MTT assay, biocompatibility tests indicated cell viability rates exceeding 98% for PVA/BN fibers, confirming their safety for biomedical applications. This study illustrates that PVA/BN composite nanofibers enhance their antimicrobial and hydrophilic properties, leading to multifunctional materials for advanced tissue engineering.Summary Electrospun PVA/BN composite nanofibers produced cost-effectively and straightforwardly. SEM images indicated that the average diameter of PVA/BN composite nanofibers was 376.26 +/- 59.20 nm. SEM and TEM analyses revealed a uniform dispersion of BNNPs within the composite nanofibers. FT-IR confirmed the presence of strong chemical interactions and the formation of unique functional groups. XRD and TEM analyses validated the structural integrity of h-BN. PVA/BN fibers exhibited inhibition zones against Escherichia coli (8.78 mm), Staphylococcus aureus (6.82 mm), and Candida albicans (21.54 mm). MIC results showed that the BN-doped composite nanofibers achieved an impressive inhibition rate of 89.56% against Escherichia coli. MTT assay (L929 fibroblast) indicated excellent biocompatibility, with over 98% cell viability rates. PVA/BN composite nanofibers show potential for advanced wound dressings and tissue engineering.
Keywords: antimicrobial; boron nitride; composite nanofiber; cytotoxicity; PVA; ELECTROSPUN NANOFIBERS; MECHANICAL-PROPERTIES; NANOSHEETS; NANOTUBES; NANOCOMPOSITES; NANOPARTICLES; PARAMETERS; HYDROGELS; DIAMETER; MATS; Materials Science; Polymer Science